Tailored co-localization analysis of intracellular microbes and punctum-distributed phagosome–lysosome pathway proteins using ImageJ plugin EzColocalization - Kang Wu (Nature Portfolio, 2021)
Abstract Immunofluorescence is indispensable to monitor redistribution of proteins involved in phagosome–lysosome association pathway-relevant (P–LApr) proteins. The software digitizing the signals of these proteins in an unbiased and automated manner is generally costly and not widely available. The open-source ImageJ plugin EzColocalization, which is for co-localization analysis of reporters in cells, was not straightforward and sufficient for such analysis. We describe here the input of custom Java code in a novel tailored protocol using EzColocalization to digitize the signals of punctum-distributed P–LApr proteins co-localized with phagosomes and to calculate percentages of phagosomes engaged. We showed that SYBR Gold nucleic acid dye could visualize intracellular mycobacteria that did not express a fluorescent protein. This protocol was validated by showing that IFN-γ enhanced the co-localization of a punctum-distributed P–LApr protein (LC3) with Mycobacterium bovis BCG in the monocyte/macrophage-like RAW264.7 cells and that there was greater co-localization of LC3 with BCG than with M. tuberculosis H37Rv in bone marrow-derived macrophages (BMDMs). Although BCG and a derived strain (rBCG-PA) showed a similarly high degree co-localization with LC3 in BMDMs, in RAW264.7 cells BCG showed much less co-localization with LC3 than rBCG-PA indicating the need for caution in interpreting biological significance from studies in cell lines.